PENGARUH GAYA KEPEMIMPINAN, SIKAP GURU DAN DISIPLIN GURU TERHADAP KINERJA GURU DI SMA/SMK - Ketut Pasek Pasek (Manajer Pendididikan, 2016)
The purposes of this research was to analyze the effect among leadership styles toward teacher performance, teachers’ attitude toward teacher performance, teacher discipline toward teacher performance and the effect leadership styles toward teacher performance, teachers’ attitude and teacher discipline toward teacher performance simultaneously in Senior Higt School PutriHijau Bengkulu Utara. The method was used is descriptive method by quantitative approach which is using simple regression analyze. The result of this showed that there were positive and significant relationship each independen variable toward dependent variable partially, and also there were positive and significan relationship leadersip style, attitude teacher, and teacher discipline toward teacher performance simultaneously in school.Keywords: leadersip, attitude, discipline, and performance